Industrial attachment report with ExxonMobile Asia Pacific Pte Ltd - Adi Dahiya (2010)
This report presents the summary of the work done by the author during the 22 weeks of his Industrial Attachment with ExxonMobil. The basic nature of the work was in the area of Information Technology in the Plant Computing Department of ExxonMobil’s Singapore Refinery. The report first introduces the basic information about ExxonMobil as a company and its operations in Singapore. The chapters that follow describe in detail the work produced by the author. The first project (section 2.1) describes the development of the Mogas DBSCN Accounting System – a standalone application developed by the user to track components blended in the Motor Gasoline (Mogas) pool in the refinery. The second project (section 2.2) exhibits the application developed by the author to serve as a business continuity model for the ExxonMobil Berth Allocation System. This application ensures the continuity and speediness of shipping transactions at ExxonMobil’s berths in case of the failure of the main application. The third project (section 2.3) enumerates the various support and troubleshooting tasks undertaken by the author. These talks not only enhanced the IT expertise of the author, but also ensured the continued reliability of network infrastructure in the refinery. Apart from the major projects, the author took the initiative to be a part of various Project Management related tasks – e.g. Risk Assessments – in his sections. The author also contributed to ExxonMobil’s safety culture by delivering February 2009’s Safety Talk to the Plant Computing Group and to conduct numerous safety observations and walkabouts in the refinery. In order to ensure brevity and contextual accuracy, the sections requiring greater detailed have been cataloged as appendices at the end of the report.